74.6k views
4 votes
10 (6x - 5) Simplify by distributing (and combining like terms if necessary).

6 (2x - 3) - 5x Simplify by distributing (and combining like terms if necessary).

2x (5 + 4) Simplify by distributing (and combining like terms if necessary).

-9 (8x - 5) Simplify by distributing (and combining like terms if necessary).

5 - 8 (3x + 5) -3

1 Answer

3 votes

Answer:

Hey there!

10(6x-5)=60x-50

6(2x-3)-5x=12x-5x-18=7x-18

2x(5+4)=18x

-9(8x-5)=-72x+45

5-8(3x+5)-3=5-24x-40-3=-24x-42

Let me know if this helps :)

User Qasim Khokhar
by
5.8k points